Use of ecological bag as a didactic resource of the "Quinzinho de Barros" zoo for the environmental education in non-formal learning spaces - Giselle Cherutti; Maria Otília J. M. Mathias; Viviane Aparecida Rachid Garcia (Universidade Estadual Paulista Júlio de Mesquita Filho, 2011)
The Sorocaba's Zoo has been developing several environmental education programs for students and for the teachers' continuing education, being one of these programs, the oriented visit. This visit has as target to promote the interaction between the public and the Zoo visitors guide during the tour by the Zoo's different areas. In this tour the ecological bags are used with the finality of showing several concepts related to the environmental conservation, this way, educating the students for the visit. This environmental project researched the application of the ecological bag as teaching and learning resource tool during the oriented visit. Two group visits of six and eight year old students from public schools were guided and oriented. The data occurred with a group which used previously the ecological bag in their respective classrooms at school, and an other group which just visited the Zoo and did not make any use of the ecological bag. The tools used were the interview and observations performed with the zoo guide, students and teachers from both groups. After analysis of the data obtained, it was concluded that the ecological bag is an important didactical resource if linked to the school activities in the assimilation of the concepts presented in this research.